A LOW-COST COLORIMETRIC DETECTION OF HG2+ USING PAPER-BASED SENSOR WITH EUCLIDEAN DISTANCE APPROACH - Muh. Supwatul Hakim; Tety Wahyuningsih Manurung; Mokhamat Ariefin; Dwi Hermayantiningsih (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2026)
Mercury (Hg) is a highly toxic heavy metal that poses significant risks to human health and aquatic ecosystems. The development of rapid and low-cost detection methods is urgently needed. In this work, the paper-based colorimetric sensor was developed by immobilizing dithizone onto Whatman No. 41 filter paper for the detection of Hg2+. The sensor utilized the color change of the sensor from green to orange with the color formation of Hg–dithizone complex. FTIR analysis confirmed the successful immobilization of dithizone with characteristic absorption of C=N and C=S vibrations. For quantification, digital images captured by a smartphone were analyzed using the Euclidean Distance (ED) approach. The sensor demonstrated a linear response in the concentration range of 1–5 mg/L (R2 = 0.991), with a limit of detection (LOD) and limit of quantification (LOQ) of 0.50 mg/L and 1.67 mg/L, respectively. Furthermore, the sensor exhibited high precision with a %RSD of 4.39%. Selectivity tests under acidic conditions confirmed that Hg2+ yielded the highest ED value compared to other metal ions such as Cu2+, Pb2+, Co2+, Ni2+, and Zn2+. This paper-based sensor provides a simple, portable, and cost-effective tool for the on-site monitoring of mercury in environmental samples